Biblical concepts and our world - Phillips, Dewi Z.; Von der Ruhr, Mario (Claremont studies in the philosophy of religion, 2004)
In this collection, distinguished theologians and philosophers of religion explore the relation of key Biblical concepts to our world. They examine a range of concepts, including authority, faith and history, the historical Jesus, the resurrection and miracles.